Assessing the forecasting performance of a macroeconomic model - Juhana Hukkinen; Matti Virén (Bank of Finland, 1996)
This paper contains a description of a small quarterly forecasting model for the Finnish economy.We evaluate the forecasting properties of the model by means of stochastic simulation involving both the endogenous and exogenous variables of the model.The simulations allow us to identify and quantify the main sources of forecasting uncertainty.We are also able to assess the linearity of the model.Forecasting performance is also analyzed in a conventional way by means of dynamic simulation.The important issue in these simulations is the stability of the model: how simulated values depend on the estimation period and the ordering of time periods.
URN:NBN:fi:bof-20140807131
Keywords: 330; forecasting; macro models; simulation